Systemic immune-inflammation index is associated with hepatic steatosis: Evidence from NHANES 2015-2018 - Song, Yancheng; Guo, Wencong; Li, Zhaopeng; Guo, Dong; Li, Zhao; Li, Yu (Frontiers in Immunology, 2022)
Background: As a novel inflammatory marker, Systemic Immune-Inflammation Index (SII) has not been studied with hepatic steatosis. The aim of this study was to investigate the possible relationship between SII and hepatic steatosis. Methods: In the cross-sectional investigation, adults having complete information on SII, hepatic steatosis, and bariatric surgery from the 2015–2018 National Health and Nutrition Examination Survey (NHANES) were included. Hepatic steatosis was evaluated with heaptic steatosis index (HSI). The platelet count × neutrophil count/lymphocyte count was used to compute SII. We investigated the independent interaction between SII and hepatic steatosis using weighted multivariable regression analysis and subgroup analysis. To explore the potential relationship between SII, bariatric surgery and hepatic steatosis by controlling potential confounders by propensity score matching. Results: The study involved 10505 participants in total, 5937 (56.5%) of whom had hepatic steatosis according to the diagnosis. After adjusted for covariates, multivariable logistic regression revealed that high SII level was an independent risk factor for hepatic steatosis (OR = 1.30, 95% CI: 1.10-1.52, P 0.01). Unexpectedly, bariatric surgery reduced SII even after PSM corrected for differences of BMI and HSI. Conclusions: In US adults, SII was positively correlated with an increase in hepatic steatosis. The SII may be a simple and affordable way to identify hepatic steatosis. Bariatric surgery may reduce SII without resorting to weight loss. This needs to be verified in additional prospective research.